Análise de Vazamentos Temporais Side-Channel no Contexto da Internet das Coisas - Prates Junior, Nelson Gonçalves; Vergutz, Andressa; Tombesi Macedo, Ricardo; Nogueira, Michele (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS); 2019: Anais do XXIV Workshop de Gerência e Operação de Redes e Serviços, 2019)
The Internet of Things (IoT) emerged because of the technologicalevolution of wireless sensor networks, which enabled these sensors to integrate with common objects. These objects are equipped with sensors and actuatorscollect data from users and the environment, process them, and transform theminto useful information. By allowing the transmission of restricted / personaldata, communication traffic between devices becomes an interesting target forattackers who either access or manipulate them. However, even with cryptographic data, side-channel attacks exploit the characteristics of devices forthe purpose of acquiring information that may compromise the security of thenetwork structure. This work presents a way of characterizing the identical IoT dispositives by only exploring the time information. It carried the activitiesout such as structuring an experimental scenario, collecting traffic, extractingstatistical characteristics and finally identifying the dispositives. The results show we can identify even identical devices with up to 100% of accuracy.